Konsepsi Dan Praktik Pendidikan Pranatal Dalam Islam - Sarno Hanipudin; Nur Alfiati (QALAM: JURNAL PENDIDIKAN ISLAM, 2021)
This study examines the concepts and practices of prenatal education in Islam, this article tries to explore the richness of Islamic science contained in nash and the opinions of Muslim scholars about prenatal education. So that the results of this study can at least add islamic insights about prenatal education as well as alternative solutions of reference sources for educational practitioners who have so far been dominant in using Western references. This research is a library research that is a pure literature research. Data collection in this study uses documentation methods that look for data on things or variables in the form of notes such as books, magazines, documents, articles, words, daily minutes, meeting notes and so on.